Differential Degradation of TRA2A and PYCR2 Mediated by Ubiquitin E3 Ligase E4B - Lu, Yao; Jiang, Bo; Peng, Kangli; Li, Shasha; Liu, Xiangnan; Wang, Bufan; Chen, Yuntian; Wang, Tiepeng; Zhao, Bo (Frontiers in Cell and Developmental Biology, 2022)
E4B belongs to the U-box E3 ligase family and functions as either an E3 or an E4 enzyme in protein ubiquitination. Transformer2A (TRA2A) and Pyrroline-5-carboxylate reductase 2 (PYCR2) are related to cancer development and are overexpressed in many cancer cells. The degradation of TRA2A and PYCR2 mediated by the ubiquitin-proteasome system (UPS) has not been reported. This study validated that E4B could ubiquitinate TRA2A and PYCR2 as an E3 ligase both in vitro and in the HEK293 cells. E4B mediated the degradation by forming K11- and K48- linked polyubiquitin chains on TRA2A and PYCR2, respectively. E4B regulated the alternative splicing function of TRA2A and affected RSRC2 transcription in the HEK293 cells. Although E4B is highly expressed, it hardly degrades TRA2A and PYCR2 in hepatocellular carcinoma (HCC) cells, suggesting other mechanisms exist for degradation of TRA2A and PYCR2 in the HCC cells. We finally reported that E4B interacted with substrates via its variable region.